The Mitochondrion-lysosome Axis in Adaptive and Innate Immunity: Effect of Lupus Regulator Peptide P140 on Mitochondria Autophagy and NETosis - Bendorius, Mykolas; Neeli, Indira; Wang, Fengjuan; Bonam, Srinivasa Reddy; Dombi, Eszter; Buron, Nelly; Borgne-Sanchez, Annie; Poulton, Joanna; Radic, Marko; Muller, Sylviane (Frontiers in Immunology, 2018)
Mitochondria deserve special attention as sensors of cellular energy homeostasis and metabolic state. Moreover, mitochondria integrate intra- and extra-cellular signals to determine appropriate cellular responses that range from proliferation to cell death. In autoimmunity, as in other inflammatory chronic disorders, the metabolism of immune cells may be extensively remodeled, perturbing sensitive tolerogenic mechanisms. Here, we examine the distribution and effects of the therapeutic 21-mer peptide called P140, which shows remarkable efficacy in modulating immune responses in inflammatory settings. We measured P140 and control peptide effects on isolated mitochondria, the distribution of peptides in live cells, and their influence on the levels of key autophagy regulators. Our data indicate that while P140 targets macro- and chaperone-mediated autophagy processes, it has little effect, if any, on mitochondria autophagy. Remarkably, however, it suppresses NET release from neutrophils exposed to immobilized NET-anti-DNA IgG complexes. In conjunction, our results suggest that in the mitochondrion-lysosome axis a likely driver of NETosis and inflammation, the P140 peptide does not operate by affecting mitochondria directly.